Depletion of tryptophan is not involved in expression of tryptophanyl-tRNA synthetase mediated by interferon. - Flohr, T (1992)
Gamma interferon (IFN-gamma) affects tryptophan metabolism by mediating the expression of indoleamine 2,3-dioxygenase and tryptophanyl-tRNA synthetase. In the present study, we investigated the role of indoleamine 2,3-dioxygenase-mediated tryptophan depletion in the induction of tryptophanyl-tRNA synthetase by IFN-gamma. The addition of excess tryptophan to the culture medium did not affect the induction of tryptophanyl-tRNA synthetase by IFN-gamma, indicating that tryptophan degradation is not directly involved in the IFN-gamma-mediated expression of tryptophanyl-tRNA synthetase.